2022
DOI: 10.1007/s10772-022-09987-4
|View full text |Cite
|
Sign up to set email alerts
|

Single-channel speech enhancement using implicit Wiener filter for high-quality speech communication

Abstract: Speech enables easy human-to-human communication as well as human-to-machine interaction. However, the quality of speech degrades due to background noise in the environment, such as drone noise embedded in speech during search and rescue operations. Similarly, helicopter noise, airplane noise, and station noise reduce the quality of speech. Speech enhancement algorithms reduce background noise, resulting in a crystal clear and noise-free conversation. For many applications, it is also necessary to process thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…DSP techniques, such as spectral subtraction, Wiener filtering, and adaptive filtering, can be used to reduce background noise and improve speech quality [62]. For example, Jaiswal et al [63] suggested a concealed Wiener filter-based technique for voice augmentation to improve the common spectral subtraction algorithm. Pauline and Dhanalakshmi [64] presented an efficient adaptive filter structure for noise reduction in voice signals that utilized the least mean square (LMS) and normalized LMS algorithms.…”
Section: Algorithms For Alaryngeal Speech Enhancementmentioning
confidence: 99%
“…DSP techniques, such as spectral subtraction, Wiener filtering, and adaptive filtering, can be used to reduce background noise and improve speech quality [62]. For example, Jaiswal et al [63] suggested a concealed Wiener filter-based technique for voice augmentation to improve the common spectral subtraction algorithm. Pauline and Dhanalakshmi [64] presented an efficient adaptive filter structure for noise reduction in voice signals that utilized the least mean square (LMS) and normalized LMS algorithms.…”
Section: Algorithms For Alaryngeal Speech Enhancementmentioning
confidence: 99%
“…Commonly used recommendation algorithms do not use many attributes for model training, because too much computational attribute information will lead to a lot of computational cost, which requires too much computational time, and cannot perform high-level feature abstraction learning and cannot be fully extracted implicit associations between data. However, if the basic information cannot be fully utilized and only interactive data such as ratings and collections are relied upon, it will easily lead to problems such as cold start and data sparseness, and cannot provide high-quality personalized recommendation services [11][12].…”
Section: The Overall Process Of the Algorithmmentioning
confidence: 99%
“…listen better. SE methods such as spectral subtraction [1], [2], Wiener filtering [3], and statistical [4], [5] have been proposed in the last few decades. These methods were computationally efficient but inadequate in dealing with nonstationary noises.…”
Section: Introductionmentioning
confidence: 99%